INTERNATIONAL CULTURAL FESTIVALS IN UZBEKISTAN: CULTURAL DIPLOMACY, HERITAGE PRESERVATION, AND CONTEMPORARY DEVELOPMENT - Teshaboyeva Nafisa Zubaydulla qizi; Baratillayeva Ruxshona Faxriddin qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the development, functions, and global significance of international cultural festivals held in Uzbekistan. It analyzes the role of festivals as instruments of cultural diplomacy, heritage preservation, creative exchange, and socio-economic growth. Focusing on music festivals, film forums, regional celebrations, and traditional events, the study explores how Uzbekistan presents its cultural identity on the world stage while fostering intercultural communication. The article also reviews contemporary challenges related to sustainability, infrastructure, and heritage protection, and highlights opportunities for strengthening Uzbekistan’s cultural presence internationally.